Empowerment after migration: Exploring the association between migration and the empowerment of women who stay behind - Ceballos, Francisco; Heckert, Jessica; Hernandez, Manuel A.; Paz, Florencia (International Food Policy Research Institute, 2024)
Migration is a recurrent global phenomenon that has rapidly increased over the past decades. As of 2020, there were 281 million international migrants (equivalent to 3.6 percent of the global population), a 27 percent increase compared to the 221 million in 2010 (UN DESA 2020). Even though COVID-19 slowed international migration, it is quickly returning to pre-pandemic levels. Approximately half of migrants are men, and a third are youth (15-24 year olds). Western Europe and the United States receive the most international migrants, and most migrants originate from rural areas, which receive around 40% of international remittances (Food and Agriculture Organization 2018). Domestically, there were around 763 million of internal migrants as of 2013, equivalent to around 12 percent of the global population (United Nations Population Division, 2013). Whether international or domestic, a large share of migrants is forced to leave their homes due to multiple reasons that include socioeconomic, climatic, and conflict factors, which may also act as compound shocks, such that migration similarly represents an important adaptation strategy that can help improve livelihoods, build resilience, and protect against fragility.